М
Молодежь
К
Компьютеры-и-электроника
Д
Дом-и-сад
С
Стиль-и-уход-за-собой
П
Праздники-и-традиции
Т
Транспорт
П
Путешествия
С
Семейная-жизнь
Ф
Философия-и-религия
Б
Без категории
М
Мир-работы
Х
Хобби-и-рукоделие
И
Искусство-и-развлечения
В
Взаимоотношения
З
Здоровье
К
Кулинария-и-гостеприимство
Ф
Финансы-и-бизнес
П
Питомцы-и-животные
О
Образование
О
Образование-и-коммуникации

X^2-15x меньше либо равно -20x-2-x^2

👇
Ответ:
ayiina264
ayiina264
27.01.2021
------------------------------
X^2-15x меньше либо равно -20x-2-x^2
4,4(32 оценок)
Открыть все ответы
Ответ:
slaadkoo
slaadkoo
27.01.2021

In the evenings            into the city and go clubbing or see a movie.
          a lot of new friends.           my pronunciation is much better already, and                almost everything. On weekdays           Liam. At the moment            on their new website and            help with it.            some useful stuff about how people        business in this country.

              to see me?            the winter holiday skiing with Ryan and Liam.              to meet you and there’s plenty of space. You must bring lots of warm clothes because            really cold here in the winter. Let me know as soon as              . And tell me what           these days.

4,6(3 оценок)
Ответ:
anna080203
anna080203
27.01.2021

ответ и Объяснение:

Нужно знать формулы сокращённого умножения:

a) a²-b² = (a-b)·(a+b);

b) (a-b)² = a²-2·a·b+b²;

c) a³+b³ = (a+b)·(a²-a·b+b²);

d) a³-b³ = (a-b)·(a²+a·b+b²);

e) (a-b)³ = a³-3·a²·b+3·a·b²-b³.

1) (a²-3)³-(a-2)·(a²+4)·(a+2) = [e)] = a⁶-3·a⁴·3+3·a²·3²-3³-(a-2)·(a+2)·(a²+4) = [a)] =

= a⁶-9·a⁴+27·a²-27-(a²-4)·(a²+4) = [a)] = a⁶-9·a⁴+27·a²-27-(a⁴-16) =

= a⁶-9·a⁴+27·a²-27-a⁴+16 = a⁶-10·a⁴+27·a²-11;

2) (b²-3)³-(b²+3)(b⁴-3·b²+9) = [e), c)] = b⁶-3·b⁴·3+3·b²·3²-3³-(b⁶+27) =

= b⁶-9·b⁴+27·b²-27-b⁶-27 = -9·b⁴+27·b²-54;

3) (m²-1)(m⁴+m²+1)-(m²-1)³ = [d), e)] = m⁶-1-(m⁶-3·m⁴·1+3·m²·1²-1³) =

= m⁶-1-(m⁶-3·m⁴+3·m²-1) = m⁶-1-m⁶+3·m⁴-3·m²+1 = 3·m⁴-3·m²;

4) (x²-2)·(x⁴+2·x²+4)-(x³-1)² = [d), b)] = x⁶-8-(x⁶-2·x³+1) =

= x⁶-8-x⁶+2·x³-1 = 2·x³-9.

4,7(42 оценок)
logo
Вход Регистрация
Что ты хочешь узнать?
Спроси Mozg
Открыть лучший ответ